From transaction marketing to relationship marketing: profiling activities throughout the customer relationship life cycle of top advertising agencies - Aliah Hanim Mohd Salleh; Mohd. Helmi Abd. Rahim (Universiti Kebangsaan Malaysian, 1995)
please refer fulltext